Ultrafast spectroscopy of nanomaterials - Zou, Xingquan (2012)
Ultrafast spectroscopy is a very useful technique to study the electronic and vibrational properties of many solid-state systems. In this dissertation, ultrafast optical-pump optical-probe (OPOP) and terahertz time-domain spectroscopy (THz-TDS) have been used to study low dimensional nanomaterials and bulk oxides which are often used substrates for nanomaterials, thin films and functional materials.